2016
DOI: 10.1111/jfpp.12847
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Digestive Properties of Protein Isolates Extracted from the Muscle of the Common Carp Using pH-Shift Processing

Abstract: This study details the nutritional and digestive properties of protein isolates that are extracted from carp (Cyprinus Carpio L.) muscle using pH shifting methods. Alkaline (ALPI) and acid (ACPI) protein isolates exhibit higher protein yields (87.6%, 76.3%, respectively). In addition to the high recovery of myofibrillar protein, a portion of the water‐soluble proteins is also recovered. The moisture contents of ACPI and ALPI are 85.5% and 88.5%, respectively, and the crude protein contents of these two fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…The statistical analysis revealed nonsignificant difference in PC due to preparation method and gender. However, the results of present study demonstrated higher PC in the protein isolates (BPI and API) than raw muscle which were consistent with the results reported by Tian et al () and Panpipat and Chaijan, (). AC was of 9.54%, 4.83%, and 6.68%, respectively, for RM, BPIs, and APIs of male common carp against 9.13%, 4.37%, and 5.45%, respectively for female was observed.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The statistical analysis revealed nonsignificant difference in PC due to preparation method and gender. However, the results of present study demonstrated higher PC in the protein isolates (BPI and API) than raw muscle which were consistent with the results reported by Tian et al () and Panpipat and Chaijan, (). AC was of 9.54%, 4.83%, and 6.68%, respectively, for RM, BPIs, and APIs of male common carp against 9.13%, 4.37%, and 5.45%, respectively for female was observed.…”
Section: Resultssupporting
confidence: 93%
“…The recovered proteins showed good color and superior functional characteristics and generally considered as safe for human consumption. Therefore, popularity of pH‐shifting method for the isolation of fish proteins is increasing now a days (Tian et al, ). The pH‐shift method includes two types of methods for the separation of muscular lipid‐free proteins from different fish species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shabanpour et al 21 reported that the protein recovery yields of silver carp and common carp during acidic and alkaline extraction were found to be 645.0 and 808.9 g kg −1 , 702.0 and 751.8 g kg −1 , respectively. The results found in this study were in agreement with the previous findings reported by Tian et al 22 and Vareltzis and Undeland 23 during the studies on common carp and blue mussel proteins.…”
Section: Protein Recovery Yieldssupporting
confidence: 94%
“…Tian et al. (2017) have indicated that surimi from common carp has more water solubility amino acids owing to the acidic/alkaline solubilization process. As regard to isoleucine and leucine, the content of these two amino acids is enhanced after ISP processing (Sun et al., 2013), which was in accordance with our results.…”
Section: Resultsmentioning
confidence: 99%